Hyperuricemia in Patients with Type 2 Diabetes at Tertiary Care Hospital - Humaira Sami Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hyperuricemia (HU) in Type 2 Diabetes Mellitus (T2DM), not only increases patient morbidity, but also lowers the quality of life, impairs functional ability, and increases mortality worldwide. Objective: The aim of this study was to find out the frequency of Hyperuricemia in patients with Type 2 Diabetes Mellitus at tertiary care hospital. Material and method: The current retrospective study was carried out at the Department of Medicine (Unit II), Bolan Medical Complex Hospital, Quetta, from 1st February 2022 to 30th January 2023. A total of 220 individuals of both genders and different age groups with type 2 diabetes mellitus were included. Data was collected using a non-probability consecutive sampling approach. Medical records were evaluated for the study without any direct patient interaction. For analysis, all of the data was collected and put into SPSS version 23. Results: The medical record of 220 individuals with type 2 diabetes mellitus were examined in the present study. The mean age of the study participants was 56.6+11.8 years. Out of which female were 130 (59%) and male were 90 (41%). The individuals in the age group of 55 years or above were 129 (58.6%). The majority of patients had poor diabetes control 168 (76.3%). Ischemic heart disease was found in 31 (14%) individuals, nephropathy was recorded in 25 (11.3%) and hyperuricemia was found in 20 (9%) of the total individuals with type 2 diabetes mellitus. Hyperuricemia was found to have a significant statistical association with diabetes duration and nephropathy, when the data was stratified by gender, age, diabetes control, or ischemic heart disease. In particular, those with diabetes for six years or longer had a greater prevalence of hyperuricemia (n=18 or 15.2%) than people with diabetes for five years or less (n=4 or 4%). Similarly, there was a substantial correlation between nephropathy and hyperuricemia (p value= 0.009). Conclusion: The present study concluded that hyperuricemia was seen in 9% of the patients with type 2 diabetes mellitus. This highlights the needs for mandatory serum uric acid screenings for all patients with type 2 diabetes mellitus. It will not only ensure early treatment for hyperuricemia, but that will in long term ultimately lead to reduction in morbidity and improvement in quality of life. Key words: Type 2 Diabetes Mellitus T2DM, Hyperuricemia HU.